2009
DOI: 10.1111/j.1365-313x.2008.03778.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MYB30 is a direct target of BES1 and cooperates with BES1 to regulate brassinosteroid‐induced gene expression

Abstract: SummaryA paradox of plant hormone biology is how a single small molecule can affect a diverse array of growth and developmental processes. For instance, brassinosteroids (BRs) regulate cell elongation, vascular differentiation, senescence and stress responses. BRs signal through the BES1/BZR1 (bri1-Ethylmethane Sulphonate suppressor 1/brassinazole-resistant 1) family of transcription factors, which regulate hundreds of target genes involved in this pathway, yet little is known of this transcriptional network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 67 publications
3
192
0
Order By: Relevance
“…For instance, BES1 and BIM1 can directly bind to the promoter regions of SAUR-AC1 and regulate its expression (37). A recent study found that AtMYB30, encoding a MYB family transcription factor, is a direct target gene of BES1, which may play an important role in the early stage of plant development (44). It was reported that BRs may play an important role in directing root epidermal cells to differentiate into hair cells or mature hairless cells in Arabidopsis (45).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, BES1 and BIM1 can directly bind to the promoter regions of SAUR-AC1 and regulate its expression (37). A recent study found that AtMYB30, encoding a MYB family transcription factor, is a direct target gene of BES1, which may play an important role in the early stage of plant development (44). It was reported that BRs may play an important role in directing root epidermal cells to differentiate into hair cells or mature hairless cells in Arabidopsis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Each hormone could influence binding of the other pathway's transcription factor through regulation of cofactors. For example, MYB77 has been shown to interact with ARF7 (Shin et al, 2007) and MYB30 has been shown to directly interact with BES1 (Li et al, 2009). An alternative explanation is that each hormone is affecting the level of the other.…”
Section: Discussionmentioning
confidence: 99%
“…HUD elements were previously reported as overrepresented in the promoters of cycling genes related to diverse hormone pathways (Michael et al, 2008). Previous studies have shown that MYB30 can directly interact with BES1, bind to a site immediately adjacent to E4, and increase induction of SAUR15 expression (Li et al, 2009). For auxin, there are 10 TGTC/GACA core elements (Fig.…”
Section: Saur15 Is Induced By Auxin and Brassinosteroid Treatmentmentioning
confidence: 99%
“…AtMYB5 regulated the outer seed coat differentiation (Gonzalez et al 2009) while AtMYB66 controlled root hair patterning. AtMYB23 regulated trichome extension and branching in combination with AtMYB5 (Li et al 2009). AtMYB16/MIXTA, is proposed to control the shape of petal epidermal cells (Baumann et al 2007), and AtMYB17 is reported to be a putative regulator of early inflorescence development and seed germination ).…”
Section: Cellular Proliferation and Differentiationmentioning
confidence: 99%
“…In seedlings, AtMYB30 has also been shown to act in the brassinosteroid pathway controlling hypocotyls cell elongation (Li et al 2009). AtMYB62 is reported to be induced in response to phosphate starvation (Devaiah et al 2009) while AtMYB108 in both biotic and abiotic stress responses (Mengiste et al 2003).…”
Section: Biotic Stressmentioning
confidence: 99%